Ściskanie Osiowe Powłoki Cylindrycznej z Równoczesnym Ciśnieniem Wewnętrznym - Klepaczko, J.; König, J.A. (Engineering Transactions, 1966)
This paper is devoted to the experimental and theoretical analysis of the problem of a cylindrical shell subjected to the simultaneous action of an axial force and an internal pressure. As a result of such a load boundary zones occur at both ends (Fig. 2). It is supposed that this effect is due to the action of moments acting in the support sections. The considerations are confined to the strain process of a shell, the problem of load at the stability loss being not analysed, this being done in other papers, such as [I, 2, 4, 5, and 6]. A tentative theoretical analysis of the effect under consideration is qiven for the elastic, elastic- plastic and plastic state. In the plastic state e material of the shell is assumed to be isotropic with a power law of strain-herdening. Some experimental results obtained with thin-walled brass tubes are quoted. The strain process of a shell was recorded until the moment of stability loss, by means of a special method based on the circumferential strain.